Oral health associates with frailty in Chinese older adults: a chain mediating model of sleep quality and depressive symptoms - Chen, Lili; Song, Junnan; Zhou, Chunrong; Su, Dan (Frontiers in Public Health, 2025)
ObjectiveWith the acceleration of the global aging process, frailty has emerged as a significant public health issue impacting the health of the older adults. Additionally, oral health problems associated with aging require urgent attention. This study aims to examine the association between oral health status and frailty in older adults and to analyze the mediating roles of sleep quality and depressive symptoms to provide recommendations for alleviating frailty.MethodsThis is a population-based cross-sectional study conducted in China from November 2024 to February 2025, involving 345 older adults aged 60 years or older. The study completed measures of sociodemographic information, oral health status, sleep quality, depressive symptoms, and frailty. Pearson correlation analysis tested the correlations between the variables, and chain mediation effects were examined using PROCESS macro (Model 6) with 5,000 bootstrap samples. Statistical significance was set at p < 0.05.ResultsThis study showed a positive correlation between oral health status, sleep quality, depressive symptoms and frailty (r = 0.457 ~ 0.583; all p < 0.001), the indirect effects of oral health status on frailty mediated by sleep quality, depressive symptoms were 0.073 (95% CI = [0.002 ~ 0.144]), 0.085 (95%CI = [0.032 ~ 0.148]), the effect mediated by both sleep quality and depressive symptoms was 0.090 (95%CI = [0.049 ~ 0.148]). The total indirect effect value of sleep quality and depressive symptoms between oral health status and frailty was 0.248 (95% CI = [0.161 ~ 0.347]), accounting for 52.54% of the total effect.ConclusionOur findings suggest that sleep quality and depressive symptoms are associated with the relationship between oral health status and frailty in older adults, indicating potential intervention targets including oral health care, sleep improvement, and mental health management to assist in slowing the process of frailty.